Periostin in Allergy and Inflammation - Sonnenberg-Riethmacher, Eva; Miehe, Michaela; Riethmacher, Dieter (Frontiers in Immunology, 2021)
Matricellular proteins are involved in the crosstalk between cells and their environment and thus play an important role in allergic and inflammatory reactions. Periostin, a matricellular protein, has several documented and multi-faceted roles in health and disease. It is differentially expressed, usually upregulated, in allergic conditions, a variety of inflammatory diseases as well as in cancer and contributes to the development and progression of these diseases. Periostin has also been shown to influence tissue remodelling, fibrosis, regeneration and repair. In allergic reactions periostin is involved in type 2 immunity and can be induced by IL-4 and IL-13 in bronchial cells. A variety of different allergic diseases, among them bronchial asthma and atopic dermatitis, have been shown to be connected to periostin expression. Periostin is commonly expressed in fibroblasts and acts on epithelial cells as well as fibroblasts involving integrin and NF-κB signalling. Also direct signalling between periostin and immune cells has been reported. The deposition of periostin in inflamed, often fibrotic, tissues is further fuelling the inflammatory process. There is increasing evidence that periostin is also expressed by epithelial cells in several of the above-mentioned conditions as well as in cancer. Augmented periostin expression has also been associated with chronic inflammation such as in inflammatory bowel disease (IBD). Periostin can be expressed in a variety of different isoforms, whose functions have not been elucidated yet. This review will discuss potential functions of periostin and its different isoforms in allergy and inflammation.